A precision prediction model for the transmission system of swing angle milling head considering machining and assembly errors. (August 2022) - Su, Lihang; Yang, Congbin; Zhao, Yongsheng; Niu, Nana; Chen, Kui
The performance of the milling head is affected by the machining and assembly process of the parts. The key to improving machining accuracy and reliability of swing angle milling head is to establish the precision prediction model. Therefore, a precision prediction model of swing angle milling head under the influence of multiple errors' sources is built. The transmission and accumulation of machining and assembly errors along the assembly sequence path for the transmission system are carried out. All essential components on the assembly sequence path are considered. In addition, the secondary impact of the bearing seat hole is also taken into account. The source of the gear assembly errors is explained. The predicted range of transmission error based on the coupling relationship between assembly errors and transmission error is obtained. A precision experiment is carried out, and the result is within the predicted range. This research demonstrates that the errors' coupling relationship considered in this paper does exist and has an effect on transmission error, which provides a new idea for calculating transmission error of other gear systems.